Autódromos ambientalmente sustentables: elementos para el control activo y pasivo del ruido (2017)
The article addresses a contemporary problem affecting thousands of cities in the world: noise, specifically, the intense noise generated by the motor sports competitions in the racetracks. It outlines the situation of some tracks in various countries, which have been limited or even closed, for not complying with noise standards required by environmental authorities. Taking as a theoretical framework the control of noise, two well-differentiated aspects are investigated: passive noise control and active noise control. In addition, and considering that the rules concerning noise is far from homogeneous at the international level, an initial research is carried out in this sense, and their results are presented. Based on these, it’s seeks to raise a formal request to the Colombian environmental authority to modify the noise threshold allowed around the racetracks.